Bridging scales in modelling and simulation of non-reacting and reacting flows. - Parente, Alessandro; De Wilde, Juray (Advances in chemical engineering, 2018)
Bridging Scales in Modelling and Simulation of Reacting Flows, Part B, Volume 53, presents key methods used to bridge scales in the simulation of reacting multiphase flows. It looks at the different aspects of such flows (transport phenomena, reactions) and includes illustrations of the methods on a variety of applications, along with the contribution of key groups in the field. Sections in this new release include multi-scale methods for fluidized bed reactors, a discussion of advances in coarse-grained discrete particle methods with industrial applications, and spatial filtering for scale bridging and its application to transport in dense bidisperse particle beds, and more.